Cash Information System Design Based on Website (Case Study on Café XYZ) - Yoga Andys Strada; Dwi Sukma Donoriyanto; Nur Rahmawati (Tibuana, 2022)
All human activities are very easy due to the rapid development of information technology. Website is a product of information technology. Currently, the use of websites has mushroomed everywhere as a promotional medium to other uses. Cafe XYZ is one of the sellers of various processed coffee drinks in Surabaya. Before the research was conducted, the cafe cashier's transaction process was still carried out in a conventional way only by relying on a notebook which was very inefficient. Not only that, it is also very difficult in the process of managing the data recap, the possibility of the data being lost is very high. The researcher offers a website-based information system design with the Laravel framework supported by a development method, namely SDLC (System Development Life Cycle) which is connected online on the internet so that it can be accessed by anyone and anywhere. With the design of this cashier website, it is hoped that it can help and simplify the transaction process, process product data collection, and also recap transaction data to be more effective and efficient and can save time and costs.